RESEARCH OF INTERDEPENDENCE OF VARIABLES AND FACTOR STRUCTURE OF MASTERS’ READINESS FOR INNOVATIVE PEDAGOGICAL ACTIVITY - Tsiuniak, Oksana; Pyslar, Anatolii; Galina , Galina; Bondarenko, Viktoriia; Kovtun, Oksana; Los, Oksana; Popovych, Ihor (Revista Inclusiones, 2020)
The purpose of the empirical study is to establish the interdependence of variables and build a factor structure of masters’ readiness for innovative pedagogical activity. The pedagogical conditions for forming the readiness of future masters to innovate in the process of training are characterized. Research methods: theoretical analysis and generalization, test methods with standardized questionnaires, factor analysis. The structure of masters’ readiness for innovative pedagogical activity is determined by factor analysis. The structure of masters’ readiness for innovative pedagogical activity combined four main factors (73.92%). It was found that the main one is F2 “cognitive readiness” (9.38%), which is positively correlated with F1 “motivational-activity readiness” (rs=.123; p≤.01), F3 “sense-vitality readiness” (rs=.204; p≤.01) and F4 “procedural readiness” (rs=.141; p≤.01). It is stated that scientific received facts give an objective understanding of the subject of the research. The received knowledge is expedient to be operationalized in the training of masters.